The Growth Path of the Hidden Champion in the Dental Medical Industry: A Vertical Single Case Study from An Innovation Ecosystem Perspective - Haiyan Li, Jie Xu, Peipei Qi (Forest Chemicals Review, 2022)
Hidden champion companies have attracted widespread attention around the world due to its high growth. In the context of anti-globalization, Chinese enterprises are facing many technical bottlenecks. Therefore, hidden champion enterprises play a key role and are a powerful propulsive force for achieving high-quality economic development in the "dual circulation" strategy and the wave of digital transformation. The growth mechanism of hidden champion enterprises has gradually become a hot issue in academic circles. Dental medical companies how to deal with the acceleration of technological innovation, the ecologicalization of business logic and the diversification of user needs under the VUCA background? This paper analyzes the various populations in the growth process of hidden champions in China’s oral medical industry and the interaction mechanism between them from the perspective of innovation ecosystem. The study finds that the innovation ecological orientation of hidden champion enterprises can achieve specialization, refinement, specialization and novelty. Furtherly to form its own core competitiveness. This paper theoretically explains the growth mechanism of hidden champion enterprises, which is of great significance for guiding and enlightening how to cultivate more hidden champion enterprises.